Academic Incentives Should Not Promote the "Extinction of Nature Experience". (1st November 2021) - Sarkar, Dipto; Chapman, Colin A.
Evidence suggests that a decline in people's exposure to nature corresponds to decreasing support for nature—a phenomenon we call extinction of nature experience. Here, we evaluate three current trends in conservation research and consider if they contribute to a decrease in exposure to nature. We suggest that while using sensors, algorithms, technocentric thinking, conducting meta-analyses, and taking more lab-based approaches all have significant potential to advance conservation goals, they lead to researchers spending less time in the field and an extinction of nature experience. A reduction of researcher field time will mean fewer local field assistants are hired and trained; lower engagement of researchers with ground realities; and a rift in conservation research, planning, and implementation. We suggest that the field of conservation science should balance how it allocates time and rewards to field versus non-field components. If we are not careful, we will select researchers that are distant from the biodiversity itself and the communities that are affecting it locally. Since the pandemic began many researchers were unable to go to their field sites and if care is not taken, the pressures that promote the extinction of nature experience may be promoted by institutions in a post–COVID-19 world.